2012
DOI: 10.1039/c2cp22715k
|View full text |Cite
|
Sign up to set email alerts
|

Structural controls on OH site availability and reactivity at iron oxyhydroxide particle surfaces

Abstract: Iron oxyhydroxides (FeOOH) are highly reactive minerals of widespread occurrence in natural and industrial settings. These minerals chiefly occur as nano- to submicron-sized particles and are covered by hydroxyl functional groups coordinated to one (-OH), two (μ-OH), or three (μ(3)-OH) underlying iron atoms. These groups are reaction centers for gases, solutes as well as solvents and thereby play important roles in the fate and transformation of natural and industrial compounds. In this work we provide tools t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
108
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(119 citation statements)
references
References 52 publications
(61 reference statements)
11
108
0
Order By: Relevance
“…However, when Fe 3+ is substituted as the central atom in the cluster, the model predicted that it would be harder to remove H from boehmite; (Supplementary Table 1 ). Conversely, experimental IR data on γ-FeOOH 48 suggests a weaker O-H bond than reported for γ-AlOOH which would suggest substituting Fe 3+ for Al would weaken the O-H bond. Given the simplicity of the model but the low concentration of Fe 3+ in the doped boehmite, it is not clear how to weight the present information.…”
Section: Resultsmentioning
confidence: 72%
“…However, when Fe 3+ is substituted as the central atom in the cluster, the model predicted that it would be harder to remove H from boehmite; (Supplementary Table 1 ). Conversely, experimental IR data on γ-FeOOH 48 suggests a weaker O-H bond than reported for γ-AlOOH which would suggest substituting Fe 3+ for Al would weaken the O-H bond. Given the simplicity of the model but the low concentration of Fe 3+ in the doped boehmite, it is not clear how to weight the present information.…”
Section: Resultsmentioning
confidence: 72%
“…Our previous work showed that −OH groups responsible for the 3667 cm −1 band are disposed along rows on dominant faces of FeOOH minerals ( Supplementary Fig. 1) 43,48 . Such rows are also exposed at the edges of sheets of Fe1 octahedra in our idealised representation of Fh (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This comparison shows that Fh generates flagship bands of poorly hydrogen bonded −OH groups (3667 cm −1 ), chemisorbed water molecules (−OH 2 ; 3690 cm −1 ) and doubly-coordinated hydroxyl groups (μ−OH; 3620 cm −1 ). Triply-coordinated μ 3 −OH sites were not detected in the expected spectral range where they occur in other crystalline iron (oxyhydr)oxide 43,45,48 minerals (cf. Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Spectroscopic techniques such as Fourier Transform Infrared Spectroscopy (FTIR) and Nuclear Magnetic Resonance (NMR) have been used to compile information pertaining to the densities and distribution of surface hydroxyls on metal (hydr)oxides [15][16][17], however with the continued advancement in computing, much of what is understood has been to a large extent gathered by a variety of mathematical modeling and chemical computation techniques [17][18][19][20][21][22][23][24][25]. For example, in a recent study, Motta et al [24] used first principle molecular dynamic simulation based on density functional theory (MD-DFT) to gain insights into the factors that influence hydroxyl reactivity at the boehmite (c-AlOOH)/water interface.…”
Section: Introductionmentioning
confidence: 99%